Laser Application in Prevention of Demineralization in Orthodontic Treatment - Sadr Haghighi, Hooman; Skandarinejad, Mahsa; Abdollahi, Amir Ardalan (Journal of Lasers in Medical Sciences, 2013)
One common negative side effect of orthodontic treatment with fixed appliances is the development of incipient caries lesions around brackets, particularly in patients with poor oral hygiene. Different methods have been used to prevent demineralization such as fluoride therapy and application of sealant to prevent caries. The recent effort to improve the resistance against the demineralization is by the application of different types of lasers. The purpose of this review article is discussing the effects of laser in prevention of demineralizationin orthodontic patients.